2017
DOI: 10.1111/saje.12182
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Risks Spillovers and Interdependence among Stock Markets: International Evidence with Covar‐Copulas

Abstract: Empirical studies have provided ample evidence on the potential benefits of international diversification with portfolios that consist of both domestic and foreign assets. This coupled with sudden and periodic crashes in global and developed equity markets have stimulated the interest of investors to diversify across markets that have the potential to provide decorrelation with global markets during turbulent periods. At the same time, international diversification may intensify cross-border listing of stocks … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 42 publications
(51 reference statements)
0
8
0
Order By: Relevance
“…With the deepening practice of risk management, the traditional value at risk (VaR) represents the maximum possible loss of the portfolio during a specific period in the future, and it can only estimate the potential risk of the asset portfolio in the benign market environment. Based on VaR, this paper introduces the concept of conditional value at risk (CoVaR) to evaluate the dynamic risk spillover effects between stock and foreign exchange markets under extreme volatility (Boako & Alagidede, 2018; Tian et al, 2022).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…With the deepening practice of risk management, the traditional value at risk (VaR) represents the maximum possible loss of the portfolio during a specific period in the future, and it can only estimate the potential risk of the asset portfolio in the benign market environment. Based on VaR, this paper introduces the concept of conditional value at risk (CoVaR) to evaluate the dynamic risk spillover effects between stock and foreign exchange markets under extreme volatility (Boako & Alagidede, 2018; Tian et al, 2022).…”
Section: Methodsmentioning
confidence: 99%
“…Based on VaR, this paper introduces the concept of conditional value at risk (CoVaR) to evaluate the dynamic risk spillover effects between stock and foreign exchange markets under extreme volatility (Boako & Alagidede, 2018;Tian et al, 2022).…”
Section: Extreme Risk Spillovermentioning
confidence: 99%
“…The first portfolio includes the three fiat currencies, EUR, GBP and YJP and the second includes the BTC cryptocurrency and the three conventional currencies. Many previous studies have tested the performance of time-varying copulas in modeling the VaR of conventional currency (Boako and Alagidede, 2018). In this section, we contribute to the existing literature by examining the impact of including cryptocurrencies on the performance of conventional currency portfolios.…”
Section: Gas Time Varying Gas Copulas and Risk Measurementmentioning
confidence: 99%
“…However, their study failed to quantify exchange rate risk. Finally, Boako and Alagidede (2018) focused on tail dependence and extreme risk spillover effects among international equity markets using CoVaR-copula. Their study found evidence of low, positively significant dependencies between African markets and their developed counterpart.…”
Section: Literature Reviewmentioning
confidence: 99%